KADAR TOTAL SENYAWA FENOLAT PADA MADU RANDU DAN MADU KELENGKENG SERTA UJI AKTIVITAS ANTIRADIKAL BEBAS DENGAN METODE DPPH (Difenilpikril Hidrazil) - Ketut Ratnayani; A. A. I. A Mayun Laksmiwati; Ni P. Indah Septian P. (Jurnal Kimia (Journal of Chemistry), 2012)
Honey contains a variety of compounds which function as antioxidants one of which is a phenolic compound. Monoflora honey used in this study were randu and kelengkeng honey from certain brand distributed on the market. Qualitative test with 5% FeCl3 result showed that both types of honey contain phenolic compounds. The total phenolic compounds was determined by spectrophotometry using the Folin-Ciocalteu method and gallic acid as standards, while the free radical activity was tested using the method of  DPPH (Difenilpikril hidrazil). The result of research showed that the total content of phenolic compound in randu was 1375,89 ± 134,10 mg GAE/kg, while kelengkeng honey was 1136,49 ± 39,62 mg GAE/kg. The % reduction of free radical in randu honey at the 5th minute was 62,55 ± 4,4407 % and at the 60th minute was 95,39 ± 8,5507 %. The % reduction of free radical for kelengkeng honey at the 5th minute was 44,12 ± 1,3433 %, 60th minute was 62,00 ± 0,8612 %, and for the standard of gallic acid the % reduction of free radical at the 5th minute was 41,03% and the 60th minute was 92,00%. Therefore, there was a linear correlation between the total phenolic compound of randu honey and kelengkeng honey with % reduction of its free radical.